Identification of functional pathways and hub genes associated with the heterochronic development of sugarcane axillary buds and sett roots through multi-omics analysis - Zheng, Jiabao; Huang, Xiaoyu; Wei, Yanli; Li, Wenyan; Chen, Baoshan; Li, Wenlan (Frontiers in Plant Science, 2025)
IntroductionSugarcane is primarily propagated for large-scale agricultural production through vegetative reproduction by planting stem cuttings. Development of sprout and sett root from the cuttings is essential for sugarcane plant to adapt to the field environment. We observed asynchronous development during the sprouting of stem cuttings in two sibling sugarcane cultivars sharing the same parent in cross breeding: the axillary buds of cultivar ZZ2 (ZZ2B) sprout earlier, while the sett roots of ZZ9 (ZZ9R) emerge sooner.MethodsComparison of the sett root architecture, soluble sugar content, plant hormone levels and gene expression profiles during sprouting.ResultsWe found that ZZ9 has a lower root cortex thickness ratio and a higher vascular cylinder thickness ratio. We also identified significant differences in the levels of soluble sugars, 3-Indolebutyric acid (IBA), N6-isopentenyladenosine (IPA), cis-Zeatin (cZ), Abscisic Acid (ABA), Gibberellin A3 (GA3), Gibberellin A7 (GA7), (±)-Jasmonic acid (JA), and N-((-)-jasmonoyl)-Sisoleucine (JA-Ile) between these cultivars. cuttings. In addition, we identified differentially expressed genes through transcriptomic analysis and discovered, via GO and KEGG enrichment analyses, that negative regulation of external stimulus response is a key to the preference of ZZ2 for early bud sprouting. The Twin-arginine translocation complex (Tat) significantly influences the preference of ZZ9’s root emergence. Furthermore, weighted gene co-expression network analysis (WGCNA) revealed that specific metabolic processes in seed coat mucilage uniquely determine the asynchronous development of sett roots and axillary buds.DiscussionThese findings provide a theoretical foundation and new perspective for understand asynchronous development in sugarcane production, offering novel insights for breeding high-quality varieties.